Management of chronic periodontitis in hypertensive patients: Penatalaksanaan periodontitis kronis pada pasien hipertensi - Hatimurni; Dian Setiawati; Afdalia Annisa (Makassar Dental Journal PDGI Makassar, 2024)
Periodontitis and hypertension have a potential relationship; both share common risk factors of smoking, stress, age, and socioeconomics. Hypertension can impact on a patient's ability to tolerate periodontal surgical treatment. This case report describes the management of chronic periodontitis in a patient with hypertensive disease. A 42-year-old female came to the Periodontia Department of RSGM Unhas with a chief complaint of maxillary front teeth that were loose and forward. Anamnesis showed that the patient had a history of hypertension. Clinical examination, 2nd and 3rd degree loose teeth in the maxillary anterior region with an average socket depth of 5 mm. Clinical examination and consultation with an internist were performed, followed by scaling, root planing and periodontal surgical treatment. It was concluded that the treatment of chronic periodontitis in hypertensive patients can be carried out by considering the patient's medical history so as to ensure appropriate modifications for safe periodontal treatment.